Escherichia coli survival and transfer in estuarine bed sediments. (3rd May 2018) - Schang, C.; Lintern, A.; Cook, P. L. M.; Rooney, G.; Coleman, R.; Murphy, H. M.; Deletic, A.; McCarthy, D.
Abstract: Bed sediment resuspension is a potential source of faecal microorganisms in the water column of estuaries. As such, it is important to identify the survival of faecal microorganisms in these bed sediments and understand how bed sediment resuspension impacts the quality of estuarine waters. This study explores the effect of bed sediment resuspension on Escherichia coli concentrations in the water column and the persistence of E .  coli in the water column and bed sediments of the Yarra River estuary in South‐Eastern Australia. Using sediment cores, we identified that the resuspension of both surficial sediments (e.g., by tidal movements) and deeper bed sediments (e.g., by large storm events) can increase E .  coli concentrations in the water column by up to 20 times in estuaries in oceanic climates. Bed sediment resuspension can result in increased E .  coli concentrations in the water column even up to 24 days after E .  coli first enters the estuarine water. This study demonstrates that faecal microorganisms, such as E .  coli, can persist for extended periods in estuarine bed sediments, which may then be re‐entrained into the water column via recreational activities, high flow events, or tidal fluctuations. If the survival and resuspension processes observed here hold true for pathogenic microorganisms, the resuspension of bed sediments may indeed represent an increased public health risk.